Pelatihan Pembuatan Media Pembelajaran dari Bahan Bekas melalui Model Project Based Learning (PJBL) Bagi Guru TK - Salwiah; Bakar, Sitti Rahmaniar Abu; Asmuddin; M, Sri Yuliani; Dima, Damsir (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
The purpose of this community service is to provide knowledge and skills for kindergarten teachers related to making learning media from used materials through the Project Based Learning (PJBL) model at Wulele Sanggula II Kindergarten. This is due to the lack of teacher initiative in utilizing used media materials in their environment to become innovative learning media that can be used in learning both inside and outside the classroom. This problem arises because there is no knowledge of partners regarding the use of used media materials such as gardus, aqua bottles, bottle caps, and others that can be converted into learning media. In addition, partners are not familiar with PJBL based learning methods that can be used in the learning process in early childhood so that learning is not monotonous. So, to overcome these problems, the methods used include socialization, practice and mentoring, and evaluation. The results of this community service are (a) teachers in partner kindergartens gain knowledge about learning media from used materials and learning models based on PJBL; (b) teachers in partner kindergartens can use learning media from used materials and learning models based on PJBL in the child's learning process; (c) teachers in partner kindergartens can design learning media for children by utilizing used materials around the environment.